Incorporation of palm oil polyol in shape memory polyurethane: Implication for development of cardiovascular stent - Zubir, SA; Saad, NM; Harun, FW; Ali, ES; Ahmad, S (Wiley, 2024)
Indexed by WOS/SCOPUS/ERA